Implementasi Manajemen Berbasis Sekolah: Analisis Keterlibatan Stakeholders di Perguruan Ahmad Yani Binjai - Kartika Kartika; Indra Prasetia; Emilda Sulasmi (UMSU, 2023)
The purpose of this research is to describe the implementation of school-based management at SMA Ahmad Yani Binjai, to analyze and describe the involvement of school stakeholders in school-based management at SMA Ahmad Yani Binjai. To analyze and describe the obstacles and achievements in implementing school-based management with stakeholder involvement at SMA Ahmad. Yani Binjai. This study uses a qualitative approach. The respondents of this study were school principals, deputy principals, teachers, school committees, parents and students. The findings of the research on the implementation of SBM at SMA Perguruan Ahmad Yani Binjai are carried out through the following stages (1) preparing SBM documents or guidelines, as the main reference in understanding school-based management (SBM), (2) implementation, through strengthening human resources (principals and teacher), (3) Evaluation and continuous improvement, the school evaluates the achievement of school goals. Schools involve stakeholders in decision making. The involvement of school members in school decision making creates transparency and healthy democracy in schools. Schools, school committees and parents are responsible for the quality of education in schools. The school's obstacle in implementing SBM is that there are stakeholders, namely understanding of the SBM concept is still low, so schools have difficulty developing various management components that exist in the school-based management concept, such as curriculum development, finance, facilities, and student affairs. The determinants of the success of SMA Perguruan Ahmad Yani Binjai is the leader of the school principal in driving SBM. One of the most important roles in school success in SBM is that the principal really understands the SBM concept. The success of Ahmad Yani Binjai Senior High School in achieving student achievement, which is an indicator of the quality of graduates, is still influenced or even determined by family factors, and even community factors, external stakeholders and the educational environment.